Analisis Prosedur Pemberian Pembiayaan Konsumtif dan Mekanisme Penyelesaian Pembiayaan Konsumtif Bermasalah Pada PT. Bank Sumut KCP Syariah Karya - Rizka Dwi Rahmadayana; Ahmad Perdana Indra (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This article aims to analyze the procedures for providing consumer financing and the mechanism for resolving problematic consumer financing at PT. Bank Sumut KCP Syariah Karya. The research method used is a qualitative research method using a descriptive approach. This research obtained primary data obtained from interviews and secondary data obtained through books, journals and other articles. The results of this research explain the procedures for providing consumer financing correctly and optimally and explain the procedures or mechanisms for resolving problematic consumer financing correctly and optimally from the process to the final stage. So that it can minimize the occurrence of problematic consumer financing.